2010
DOI: 10.1111/j.1365-294x.2009.04474.x
|View full text |Cite
|
Sign up to set email alerts
|

Finding a (pine) needle in a haystack: chloroplast genome sequence divergence in rare and widespread pines

Abstract: Critical to conservation efforts and other investigations at low taxonomic levels, DNA sequence data offer important insights into the distinctiveness, biogeographic partitioning and evolutionary histories of species. The resolving power of DNA sequences is often limited by insufficient variability at the intraspecific level. This is particularly true of studies involving plant organelles, as the conservative mutation rate of chloroplasts and mitochondria makes it difficult to detect polymorphisms necessary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 69 publications
2
91
1
Order By: Relevance
“…This result is consistent with previous studies showing low within-population diversity in addition to limited gene flow among populations in C. debaoensis 1011. Whittall et al 49 found a comparable level of intraspecific divergence in pines, irrespective of the rarity of the considered species. However, in the pest species Jacobaea vulgaris (Asteraceae), the intraspecific divergence was four times higher50, perhaps due to it’s short generation times as opposed to those prevailing in slow growing and long-lived trees.…”
Section: Resultsmentioning
confidence: 87%
“…This result is consistent with previous studies showing low within-population diversity in addition to limited gene flow among populations in C. debaoensis 1011. Whittall et al 49 found a comparable level of intraspecific divergence in pines, irrespective of the rarity of the considered species. However, in the pest species Jacobaea vulgaris (Asteraceae), the intraspecific divergence was four times higher50, perhaps due to it’s short generation times as opposed to those prevailing in slow growing and long-lived trees.…”
Section: Resultsmentioning
confidence: 87%
“…The cp genomes of Panicum virgatum , which has different ecotypes in upland and lowland regions, contained 116 SNPs and 46 indels [10], and high variability in indel (3–278) and SNP (6–1000) numbers was noted in the cp genomes of 13 Gossypium species [11]. Finally, comparison of intraspecific variation in rare and widespread pines indicated low levels of divergence [8]. These data improved our understanding of cp genome evolution and divergence times of closely related taxa.…”
Section: Introductionmentioning
confidence: 96%
“…A total of 10 pmol was used for 76 cycles of paired-end sequencing in a single lane of an Illumina GAI in the Central Service Laboratory of the Oregon State University Center for Genome Research and Biocomputing. Assembly of the microreads followed a modified protocol of Whittall et al [26]. Microreads, after tag removal, were assembled into contigs with the de novo assembler Velvet v. 0.7 [27].…”
Section: Methodsmentioning
confidence: 99%